Murder at Half Moon Gate - Penrose, Andrea (Penrose, Andrea. Wrexford & Sloane historical mystery., 2018)
"When Lord Wrexford discovers the body of a gifted inventor in a dark London alley, he promptly alerts the watchman and lets the authorities handle the matter. But Wrexford soon finds himself drawn into the murder investigation when the inventor's widow begs for his assistance, claiming the crime was not a random robbery. It seems her husband's designs for a revolutionary steam-powered engine went missing the night of his death. The plans could be worth a fortune...and very dangerous in the wrong hands"--Amazon.com.